PERAN ORDER TAKER DALAM HOUSEKEEPING: MENINGKATKAN KUALITAS PELAYANAN KEPADA TAMU DI RENAISSANCE HOTEL & RESORT OKINAWA - Bagus Agil Septian; Tuwuh Adhistyo Wijoyo (Universitas Bina Taruna Gorontalo, 2024)
The aim of this study is to gain a better understanding of the role of Order Taker in improving the quality of Housekeeping services at the Renaissance Hotel & Resort Okinawa. In addition, the study also tries to identify problems faced by staff and ways to address them. Methods: This research is designed as descriptive qualitative research. Data is collected through interviews, observations, and literary studies. The result of this research is that Order Taker helps improve the quality of Housekeeping services by receiving and processing guest requests in a timely and efficient manner. Handle guest complaints in a friendly and professional manner. Give me a polite and friendly service. Create a positive relationship with the guests. Using technology to be more efficient. Maintain the comfort and hygiene of the guest room. Obstacles: Order Taker faces many challenges, including high work pressure, lack of technological support, mismatch with Housekeeping staff, and lack of training and motivation. Strategy: To overcome this problem, you can use technology, manage workloads, and improve communication. Team coordination, training, and incentives.